The temporal structure of multiple visuomotor processes in baseball batting: insights from a virtual reality system - Saijo, Naoki; Fukuda, Takehiro; Kashino, Makio (Frontiers in Psychology, 2025)
Baseball batting is an inherently complex visuomotor task that requires the rapid processing of multiple cognitive-motor computations within a split second. The key components of these computations include the sense of timing, swing decision-making, and swing adjustment. Although each of these components has been studied independently, few studies have addressed their temporal integration. As such, we explored the temporal structure of visuomotor processes in baseball batting using a virtual reality (VR) batting training system. The VR system simulated a mixed sequence of fastballs and breaking balls in which participants were instructed to swing at strikes or take at balls, thus mimicking a real pitcher-batter scenario. The sequence also included pitches where the ball became occluded midway, requiring the participants to maintain accurate swings. Twenty-three batters from a professional Japanese baseball team participated in this experiment. They exhibited the ability to adjust swing timing based on pitch speed, make swing decisions based on strike/ball discrimination, and adjust swing trajectories according to the ball plate location. However, we observed performance deterioration with occluded pitches, particularly in the swing trajectory adjustment, which significantly declined. Swing decision-making showed minor decline, whereas swing timing adjustment remained unaffected. These results indicate that an occluded ball trajectory affects swing adjustment and partially impacts swing decision-making. These findings suggest a temporal structure in the brain’s processing: After the start of pitching, the batter’s brain first handles the computations for swing timing adjustment, followed by swing decision-making, and finally swing trajectory adjustment. Furthermore, the results highlight the potential of VR training systems as powerful tools for elucidating the intricate mechanisms underlying athletic skills.